Nest architecture development of grass-cutting ants - Forti,Luiz Carlos (2018)
ABSTRACT Atta bisphaerica is a species of grass-cutting ants commonly found in the Cerrado biome. The Brazilian Cerrado (savanna) biome covers 2 million km representing 23% of the area of the country. It is an ancient biome with rich biodiversity, estimated at 160,000 species of plants, fungi and animals. However, little is known about their nest architecture development. This study investigated the architecture of fourteen A. bisphaerica nests from Botucatu, São Paulo, Brazil. Molds were made of the nests by filling them with cement to allow better visualization of internal structures such as chambers and tunnels. After excavation, the depth and dimensions (length, width, and height) of the chambers were measured. As expected, there was a lateral development in the nests and increase in the number of chambers over time. Results showed that in nests with an estimated age of 14 months, the average depth was 1.6 ± 0.4 m; for those with 18 months it was 2.2 ± 0.7 m and at 28 months it was 2.5 ± 0.7 m. The number of chambers varied from 4 to 7 in 28-month nests, 2 to 4 in 18-month nests, and from 2 to 3 in 14-month nests. With respect to the dimensions of the internal tunnels, there were variations in their average width, increasing with time. The fungus chambers were located beneath the largest mound of loose soil. This study contributes to a better understanding of the so far unknown nest architecture development of A. bisphaerica grass-cutting ants.